THE EFFECTS OF EXPERIENCE AND TASK-SPECIFIC KNOWLEDGE ON AUDITOR’S PERFORMANCE IN ASSESSING A FRAUD CASE - MEIRYANANDA PERMANASARI; INDRA ARIFIN DJASHAN (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2012)
This research’s objective is to investigate the relationships of auditor’s experience, task-specific knowledge gained from training, and auditor’s performance. This study explores whether the experience or the task specific knowledge variable or even the combination from both of them gained the auditor’s performance in assessing a fraud case. This research used 16 CPA firm samples that consist of 141 external auditors. This research used normality test, independent sample t-test, one way ANOVA. This result of this research shows that there is no difference between combination of experience and task-specific know-ledge on auditors’ performance in assessing a fraud case. For the task specific knowledge there is difference between the auditor who has training and without training on auditors’ performance in assessing a fraud case. And the last there is no difference between the auditor who worked less than a year, more than a year but less than 2 years and more than 2 years on auditors’ performance in assessing a fraud case.